Control of Cladosporium Leaf Spot of Poplars in the Nursery - Khan, S. N.; Tivari, R. K.; Misra, B. M.; Rawat, D. S. (Indian Forester, 1990)
Experiments were conducted to evaluate different fungicides against Cladosporium humile J.J. Davis, a serious foliage pathogen of poplars and to study disease development in Shilli Nursery, Solan (H.P.). Dithane M-45(0.35%) was found most effective followed by a mixture of Dithane M-45 and Bavistin (0.2 and 0.05% respectively) and Dithane M-45 (0.25%) Disease development studies revealed that the pathogen overwinters on the fallen leaves, dormant buds, in lenticels and bark crevices of the standing plants. The infection begin to appear on the plants in the month of May and progressed to a highest disease index in November. Measures to control and contain the disease have been suggested.